135 Ventilatory Support in Patients with Central Hypoventilation Syndrome (CHS) - Results of the EU-CHS Network Survey. (October 2012) - Migdal, M; Trang, H; Peters, J; Katz-Salamon, M; Ottonello, G; Samuels, M
Abstract : Background and aim of the study: Aim of the study was to identify the European centers for diagnosis and treatment of patients with CHS and to collect information on type of ventilatory support currently used for this group of patients. Method: The survey was performed in countries participating in the EU-CHS network project. Using a special template following information were collected: total number of already diagnosed patients, number of currently treated patients, type of ventilatory support (invasive ventilation via tracheostomy, mask ventilation, diaphragm pacing, negative ventilation). Results: The survey was performed during 2011. Replies were received from 15 centers located in 10 European countries. Number of CHS patients already diagnosed and currently treated varies significantly between centers (from 2 to 112 and from 1 to 70 respectively). Total number of already diagnosed CHS patients were 305 and 199 of them are currently treated. Most frequently used type of ventilator support is ventilation via tracheostomy (52% of patients). Diaphragm pacing alone or diaphragm pacing and ventilation is currently used in 42 patients. Only one CHS patient is currently treated with negative pressure ventilation. Conclusions: Results of this study have shown existing significant differences (mainly number of patients) but also some similarities (type of ventilatory support) between centers for CHS diagnosis and treatment located in 10 different European countries. All of the collected data should be used for further work on the European CHS network of reference centers. The study was supported by the EU-CHS Network (grant number 2008 12 06).